Stability of chilli genotypes for different seasons at terai zone of West Bengal - J C Jana, S Datta, (Journal of Spices and Aromatic Crops, 2012)
The stability of 15 chilli (Capsicum annuum L.) genotypes, was studied during rabi (winter) and kharif (rainy) seasons of 2005-06 and 2006-07 at Pundibari, Cooch Behar (West Bengal). Pooled analysis of variance revealed the presence of significant genetic variability among the genotypes. With respect to different growth, yield and quality characters, significant differences were also found in all the characters except ascorbic acid, indicating the effect of environment on the performance of the genotypes. Ulka-686 showed supremacy in yield in both rabi and kharif seasons but its magnitude of yield for kharif season was about half of that of rabi season. CA-29 exhibited better performance under rabi season and Jwalan, Tejaswini and Pusa Sadabahar were adapted for kharif season.